Sensorimotor life an enactive proposal - Di Paolo, Ezequiel A. 1970-; Buhrmann, Thomas; Barandiaran, Xabier 1969- (Oxford Scholarship Online Psychology, 2017)
Based on recent theoretical developments in the enactive approach to life and mind, this book elaborates a series of contributions to a non-representational theory of action and perception. These enactive ideas are applied and extended to provide a theory rich, naturalistic account of the sensorimotor meaning and agency